Child Protection in England, 1960-2000 Expertise, Experience, and Emotion - Crane, Jennifer (Palgrave Studies in the History of Childhood, 2018)
History; Social history; Great Britain-History; Europe-History-1492-; Social policy; Childhood; Adolescence